Discovery and engineering of small SlugCas9 with broad targeting range and high specificity and activity. Issue 7 (15th March 2021) - Hu, Ziying; Zhang, Chengdong; Wang, Shuai; Gao, Siqi; Wei, Jingjing; Li, Miaomiao; Hou, Linghui; Mao, Huilin; Wei, Yanyan; Qi, Tao; Liu, Hongmao; Liu, Dong; et al.
Abstract: The compact CRISPR/Cas9 system, which can be delivered with their gRNA and a full-length promoter for expression by a single adeno-associated virus (AAV), is a promising platform for therapeutic applications. We previously identified a compact SauriCas9 that displays high activity and requires a simple NNGG PAM, but the specificity is moderate. Here, we identified three compact Cas9 orthologs, Staphylococcus lugdunensis Cas9 (SlugCas9), Staphylococcus lutrae Cas9 (SlutrCas9) and Staphylococcus haemolyticus Cas9 (ShaCas9), for mammalian genome editing. Of these three Cas9 orthologs, SlugCas9 recognizes a simple NNGG PAM and displays comparable activity to SaCas9. Importantly, we generated a SlugCas9-SaCas9 chimeric nuclease, which has both high specificity and high activity. We finally engineered SlugCas9 with mutations to generate a high-fidelity variant that maintains high specificity without compromising on-target editing efficiency. Our study offers important minimal Cas9 tools that are ideal for both basic research and clinical applications.